'What script am I meant to use?': a qualitative study in chronic primary pain - Niamh Blythe; Carmel Hughes; Nigel D Hart (BJGP Open)
Background: Chronic primary pain (CPP) as a diagnosis has been introduced in the recent International Classification of Diseases, 11th Revision (ICD-11). CPP captures the experience of pain as the primary problem, without an underlying attributable cause. Dissemination of UK guidance regarding CPP represents the first time it has been recognised as a condition in its own right. Little is known about GP views concerning caring for patients with CPP, and how related guidance is viewed and applied in practice. Aim: To explore GP perspectives in relation to caring for people with CPP, including challenges encountered and use of related guidelines in practice. Design & setting: A UK-wide qualitative interview study in primary care. Method: Purposive and snowball sampling were used to recruit 15 GP participants from England, Northern Ireland, Wales, and Scotland. Semi-structured interviews were undertaken and analysed using reflexive thematic analysis. Results: The following three main themes were generated: (1) 'How to start? Problematic beginnings', which referred to difficulties regarding diagnosis; (2) 'Where to go? Mapping the management challenge'; and (3) 'How to get there? Navigating strategies and response', which explored GP awareness and acceptability of UK guidelines for chronic pain. Areas identified for potential improvement included increased access to non-pharmacological management (NPM) and secondary care services, support with deprescribing, and an expanded multidisciplinary team input. Conclusion: CPP is complex to both diagnose and manage. Although guidelines provide a useful framework, they pose challenges when translating into day-to-day practice.